A model of poststroke fatigue based on sensorimotor deficits. Issue 6 (December 2015) - Kuppuswamy, Annapoorna; Rothwell, John; Ward, Nick
Abstract : Purpose of review: This review examines recent studies in poststroke fatigue that might contribute in understanding the pathophysiology of poststroke fatigue. Poststroke fatigue is a common problem in stroke survivors. Little is known about the pathophysiology of chronic fatigue in stroke survivors. It has long been thought of as a neuropsychiatric problem. However, there is gathering evidence to the contrary. In this study, we propose a new model of poststroke fatigue based on recent findings of corticomotor neurophysiological, behavioural, and perceptual deficits in the poststroke fatigue population. Summary: The current evidence suggests that poststroke fatigue may not be a neuropsychiatric problem but a problem of the sensorimotor system. Future studies need to address the causal link between sensorimotor deficits and poststroke fatigue.